Injury in the Women's National Basketball Association (WNBA) From 2015 to 2019 - Hayden Baker, M.D; Andrew Rizzi, M.D; Aravind Athiviraham, M.D (Elsevier, 2020)
Purpose: To provide an overview of the injuries suffered by Women's National Basketball Association (WNBA) athletes and to analyze the demographic data, injury rates, and games missed as a result of individual injuries. Methods: Using publicly available data on WNBA player's injury history, we generated a database cataloguing the quantity, location, frequency, and longitudinal impact of injuries sustained during the WNBA regular season from 2015 to 2019. We analyzed the data using SPSS-25 data manipulation software to assess the number of injuries per athletic exposure. Results: Lower-extremity injuries (n = 143, 73%) were the most common injury by body area and resulted in the greatest number of games missed (n = 1189, 88%). Lateral ankle sprains were the most frequent injury (n = 39, 20%), with a rate of 1.19 injuries per 1000 athletic exposures. Torn anterior cruciate ligaments (n = 18, 9.2%) were the most devastating, resulting in the greatest number of games missed (n=376, 28%). Conclusions: Our findings corroborate previous notions that lower-extremity injuries are the greatest source of injury in this population. Ankle injuries were the most frequent injury reported by pathology, while knee injuries carried the most long-term impact on games missed due to injury. Level of Evidence: IV, Epidemiological study